“SERBIAN SOKOL” IN BARBERTON (OHIO) (GYMNASIUM, 2017)
Serbs in America during 1909 began to accept Sokol idea started in 1862 in Prague (Czech Republic). That is the time when also appeared the first initiatives for founding of Serbian Sokol Societies. In the second mid of 1909 two societies were formed, and in the next 1910 five more, so until the end of that year seven societies were active. Serbian Sokol Society in Barberton was founded in 1910, as fifth in a row. After forming of Serbian Sokol District (Union) in America (Union of all Serbian Sokol Societies in America), on October 2nd 1911 in Gary, Society from Barberton became its member. During their existence and work, Sokols from Barberton gave significant contribution to not only Serbian, but also Slavic Sokolism in America. The goal of this research is to highlight and tear off from oblivion formation, work and contribution of this Sokol society to development of Sokolism in America. Numerous primary and secondary historical sources originated in the time of societies’ existence as also the ones originated later, were reviewed and analysed.